2018
DOI: 10.1371/journal.pone.0204661
|View full text |Cite
|
Sign up to set email alerts
|

Simulated nitrogen deposition significantly reduces soil respiration in an evergreen broadleaf forest in western China

Abstract: Soil respiration is the second largest terrestrial carbon (C) flux; the responses of soil respiration to nitrogen (N) deposition have far-reaching influences on the global C cycle. N deposition has been documented to significantly affect soil respiration, but the results are conflicting. The response of soil respiration to N deposition gradients remains unclear, especially in ecosystems receiving increasing ambient N depositions. A field experiment was conducted in a natural evergreen broadleaf forest in weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 63 publications
4
21
0
Order By: Relevance
“…The +N treatment decreased the rate of litter decomposition in our study, supporting our first hypothesis that N addition would decrease litter decomposition in the study forest. This result was in agreement with most of the previous studies in subtropical forests [21,28]. This phenomenon can be explained by two mechanisms.…”
Section: Rate Of Litter Decompositionsupporting
confidence: 93%
See 3 more Smart Citations
“…The +N treatment decreased the rate of litter decomposition in our study, supporting our first hypothesis that N addition would decrease litter decomposition in the study forest. This result was in agreement with most of the previous studies in subtropical forests [21,28]. This phenomenon can be explained by two mechanisms.…”
Section: Rate Of Litter Decompositionsupporting
confidence: 93%
“…In this study, we carried out a two-year field experiment in a subtropical evergreen broadleaved forest in this rainy area to examine the responses of the litter decomposition and the release of C, N, and P to the addition of N and S. The aims of this study are to improve the understanding of the effects of N and S deposition on litter nutrient release in subtropical evergreen broadleaved forests in the studied area and to provide a reference for the management of these forests under the scenario of a sustained rise in N and S depositions. Previous studies in broadleaved forests in this rainy area have shown that the addition of N decreased soil microbial biomass [27][28][29] and the activities of soil C-cycle enzymes [30], suggesting that N input may negatively affect litter decomposition and nutrient release [21,31,32]. We thus hypothesized that (1) N addition would inhibit litter decomposition and decrease the release of C, N, and P in the study forest.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…(Chen et al 2018a;, soil respiration) and decomposition of litter(Whittinghill et al 2012;Cenini et al 2016). In our previous studies in the same region, we reported that N addition signi cantly suppressed soil heterotrophic respiration(Wei et al 2020), and decomposition of litter and the degradation of lignin and cellulose(Zhou et al 2018;Tie et al 2020a). …”
mentioning
confidence: 87%